How participating in sports causes manifestations and mimics of allergic conditions and what to do about them for optimum performance - Weiler, J. M.; Greenberger, P. A. (The Journal of Allergy and Clinical Immunology, 2020)
This theme editorial reviews and outlines 7 manuscripts published by the Journal of Allergy and Clinical Immunology: In Practice 2020 titled Sports Allergy. One goal of this project is to identify how to diagnose correctly, treat effectively, and optimize health care outcomes for people of various ages and skill levels, who participate in sports activity and develop respiratory symptoms. Of course, not all activities that produce wheezes or chest tightness during exercise are from bronchoconstriction, and articles in this issue explore the differential diagnosis and approaches to treatment.